Designing electronic systems for EMC - Duff, William G. (Raleigh, NC SciTech Publishing, 2011)
This book reviews developments in the following topics: electronic system design; EMC; shielding theory; protection technique; bonding; grounding; filter; ferrite; isolator; transient suppressor; cable; and connector.
Electronic reproduction.
Keywords: Bonding; Electric cables; Electric connectors; Electromagnetic compatibility; Shielding (Electricity).; Electronic books